FORMULATION AND ACCEPTABILITY OF SIOMAY WITH SUBSTITUTION EUCHEUMA COTTONI SEAWEED PUREE AS A HIGH-FIBER SNACK - Nathasa Weisdania Sihite; Manuntun Rotua (GEMA KESEHATAN, 2022)
Research by the Institute for Health Measurement and Evaluation (IHME) in 2014 stated that obese people worldwide increased to 2.1 billion in 2013. Factors determining weight gain problems include high energy intake that exceeds needs, such as fast food consumption, ice cream, fries, and burgers. Seaweed is known to be high in fiber and is very well used as a food raw material to overcome the problem of weight gain. Siomay is a food favored by all people in Indonesia. The research aimed to analyze the acceptability of seaweed puree formulation into dumpling products. This study is experimental with a completely randomized design (CRD) with four treatments, namely F0 (0%), F1 (25%), F2 (45%), and F3 (55%), with two replications. The panelists in this study consisted of 30 people. The results showed that the acceptability of siomay products with the addition of seaweed puree, which on the attributes of color (p = 0.948), aroma (p = 0.401), texture (p = 0.074), and aftertaste (p = 0.561) did not have a significant effect on product quality. Meanwhile, based on the results of the acceptance test on taste, it was found that there was a significantly different effect (p = 0.044) on dumpling products with the addition of seaweed puree formulations with various concentrations. Results of the product acceptability analysis show that seaweed dumplings with the addition of 45% seaweed puree (F2) are the most preferred and selected formula in this study. Keywords: Acceptability, Formulation, Puree, Seaweed, Siomay